The Impacts of COVID-19 Pandemic on the sustainability of sports tourism destinations: Evidence from Isfahan province in Iran - Marjan Amini; Hassan Bahrololoum; Reza Andam; Taha Rabbani (Research in Sport Management and Marketing)
Purpose: Following the pandemic of Covid-19, many sports tourism destinations rendered stagnant. The ambiguity of the disease and its unanticipated outbreak came as a surprise to policymakers in tourism centers. Many uncertainties about the dimensions and how this disease affects tourism destinations, arise the need to scrutinize it prospectively. Therefore, present study attempts to focus on the "sustainability" component of tourism destinations along with the situation of sports tourism in Isfahan province in the next 10 years (2031). Methods: By adopting a quantitative-qualitative approach and using the futuristic method, data was collected from a number of sources including experts’ interviews, questioning citizens of Isfahan province and documentary studies. Data analysis was performed by open and axial coding, cross-impact analysis and scenario planning. Results: In total, 40 drivers for the future of sports tourism in Isfahan province were identified. Based on four critical uncertainties with two assumptions for each, a total of 16 plausible scenarios were obtained and it was found that the second, seventh and fourteenth scenarios are more likely to occur. In these scenarios, a gradual increase in social responsibility is expected along with the development of technology. However, economic investment and institutional policy making are at their worst, and so we will see the current trend in pandemic control maintains. This issue threatens the sustainability of sports tourism destinations in Isfahan province. Conclusion: The most significant presupposition for achieving sustainability in sports tourism destinations is a review of crisis management policy at national and state levels.